Sistem Pemerintahan Berdasarkan Atas Undang - Undang Dasar 1945 Dalam Prospek Perkembangan Demokrasi - Indrastuti, Lusia - (Exsplorasi, 2011)
ABSTRACTThis research aims to analyze and to respond to the implementation of constitution 1945 (UUD 1945) based governmental system in indonesia, particularly in the light of democractic development prospect. The main topic raised in this research is the implementation of Constitution 1945 (UUD 1945) which is established as a Supreme Law which consultitutionally bounds by PPKI (Indonesian Committee for Independence) that has been amended four times.